The psychometric properties of interpersonal support evaluation list-short form (ISEL-16) on College Students - Wahyu Rahmanto, Septian (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
The Interpersonal Support Evaluation List (ISEL) is an instrument for assessing perceived social support. It exists in both full and short forms, with the short version (ISEL-16) offering practical advantages in terms of efficiency for assessments and research. To date, there is no adapted version of the ISEL-16 available in Indonesian. This study aimed to adapt and validate the ISEL-16 for use in Indonesia through psychometric analysis. The adaptation process followed ITC guidelines, including obtaining permission, conducting back-to-back translations, evaluating language comparability and interpretability, and testing the instrument on a sample population. 292 active students were recruited using quota sampling. Validity and reliability were assessed using Confirmatory Factor Analysis (CFA) in AMOS 23. Results indicated that the ISEL-16 exhibits a good model fit with four factors: appraisal, tangible assets, belonging, and self-esteem. The findings confirm that the Indonesian version of the ISEL-16 is a valid and reliable measure of perceived students’ social support. Theoretically, the adaptation reinforces the four-dimensional structure of social support previously established. Practically, it can be used to predict stress-related outcomes, such as crisis-related and academic stress, and is recommended for time- and resource-constrained research scenarios as well as for classical tests or exploratory studies.